Kevalidan dan kepraktisan Pengembangan Media Gunung Meletus dari Bubur Kertas Materi Mitigasi Bencana untuk Siswa Kelas 4 Sekolah Dasar - Wulandari, Amelia Putri; Istiq’faroh, Nurul; Andini, Nuni Maryana (CV. Kurnia Grup, 2026)
This study aims to develop a learning medium in the form of a paper pulp model of a volcanic eruption for disaster mitigation lessons integrated into fourth-grade Indonesian language classes in elementary school, as well as to test its validity and practicality. As a country prone to volcanic eruptions, Indonesia requires concrete and interactive learning media so that fourth-grade students, who are at the concrete operational stage, can understand the process of volcanic eruptions and mitigation efforts. The model is made from paper pulp, which is inexpensive, easily obtainable, and environmentally friendly, and is equipped with a simple simulation mechanism to depict the flow of lava caused by magma pressure. The study employed a Research and Development (R&D) approach, comprising the following stages: needs analysis, design, prototype development, expert validation, revision, and limited testing. Validation was conducted by fourth-grade teachers using a 1–4 scale validation sheet covering five aspects (practicality, appearance, feasibility, safety, and content appropriateness).Practicality was assessed through teacher observations and student questionnaires administered to 23 fourth-grade students. The validation results showed an average score of 4.00 (Highly Valid) across all aspects. The practicality of the media reached 95% (Highly Practical) according to teachers, and an average score of 3.8 (Highly Practical) according to students. This media proved suitable for use without revision, easy to operate within 2 × 35 minutes, and capable of increasing student engagement and understanding of disaster mitigation material in a concrete and enjoyable way. This study provides an economical and contextual alternative media made from local materials for teachers in disaster-prone areas.